Medicine meets virtual reality: health care in the information age. [San Diego, Calif., 1996] - Weghorst, Suzanne J.; Sieburg, Hans B.; Morgan, Karen S. (Studies in health technology and informatics, 1996)
The main topic of this work is: Health Care in the Information Age: Future Tools for Transforming Medicine. Medicine Meets Virtual Reality is a publication for medicine and interactive technology to interface and create the future of health care